Novel plant-derived macroporous scaffolds - Mohammed Shahrudin Ibrahim (Nanyang Technological University, 2022)
Pollen is generated in large amounts in flowering plants, but a majority of these end up as biological waste. Harvesting and modulating the properties of pollen could potentially turn pollen into a sustainable source of materials with specialized purposes. A facile method to transform robust pollen grains into soft microgel by was optimized. Utilizing a range of characterization techniques, marked increase in the level of carboxyl groups present in the intine and reduced Young’s modulus of the exine gave rise to pollen with tunable mechanical characteristics resembling microgels, while exhibiting physical properties that rapidly respond to stimuli, reminiscent of smart polymers. The ability of pollen microgels to form 3D porous sponges via freeze-drying and the various factors that influence the sponge characteristics were investigated. Regulation of stiffness of pollen microgels, the swell state of the microgels and the freezing rate of the microgel slurry greatly influence the morphology, porosity, hydrophilicity and compression modulus of the fabricated 3D sponges. Stearic acid functionalization of optimized pollen scaffolds demonstrated good absorption to a variety of known organic solvent contaminants of water, with comparable performance to commercial synthetic polymer‐based absorbents and an improved environmental footprint.